Art. 72 TFEU as Seen by the Court of Justice of the EU: Reminder, Exception, or Derogation? - Hubert de Verdelhan (European Papers, 2025)
(Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1330-1364 | Article | (Table of Contents) I. Introduction. – II. Art. 72 TFEU: no “general exception” from the scope of EU law. – III. Art. 72 TFEU: a reminder for the EU institutions. – IV. Art. 72 TFEU: a derogation to the benefit of the Member States? – V. Conclusion. | (Abstract) When the Member States of the European Union (EU) transferred to the latter the competences necessary to put in place an Area of Freedom, Security and Justice (AFSJ), they accepted that the EU determines policies on matters such as immigration and border control, which those States otherwise consider not only as sovereign, but also to be related to their security. Yet, the Member States were careful to lay down safeguards for their interests. Art. 72 TFEU constitutes one of those safeguards. That provision, which states that the development of AFSJ policies and instruments “shall not affect the exercise of the responsibilities incumbent upon Member States with regard to the maintenance of law and order and the safeguarding of internal security”, has been the focus of a recent series of decisions from the Court of justice of the European Union (CJEU). It stems from those decisions that, while art. 72 TFEU does not exclude national measures implemented for the purposes of maintenance of law and order or safeguarding internal security from the scope of EU law, that provision has two functions. First, it serves as a reminder of those responsibilities for the EU institutions. As such, it compels, inter alia, the EU legislature to ensure that AFSJ instruments leave a genuine possibility for the Member States to exercise them. Secondly, art. 72 TFEU could also, theoretically, justify Member States departing from AFSJ instruments in certain “exceptional circumstances”.